Environmental geological evaluation of areas for sanitary landfill in the cities of Urubamba, Ollantaytambo and Machu Picchu, department of Cusco - Allende Ccahuana, Teófilo (2002)
The towns of Urubamba , Ollantaytambo and Machu Picchu Cusco department suffer the problems of environmental sanitation by disposal of solid waste without technical criteria . Furthermore, the existence of collection points converted into garbage dumps that are distributed in the marginal urban and urban area of these cities , causing the deterioration of air, water and soil and the risk to the health of people . In order to overcome the environmental problems in the management of solid waste , local authorities proposed areas where they can build a landfill to benefit the three cities located near Yuncacha Huayco sector in the district of Maras, and in Algarrubillo in the district of Ollantaytambo. With environmental geological evaluation found that the areas of the sector Yuncacha Huayco and Algarrubillo will have climatic, hydrological , topographical and geological to manage a health project properly conditions, which would justify making economic investments and control pollution of the environment region , and apparent restrictions on land use and land ownership .